Hunters' response to chronic wasting disease in four states - Lyon, Katie M., author; Vaske, Jerry J., 1951-, advisor; Donnelly, Maureen P., committee member; Wilson, Kenneth R. (Kenneth Ray), committee member (Colorado State University. Libraries, 2011)
Chronic wasting disease (CWD) is a fatal transmissible spongiform encephalopathy (TSE) found in deer, elk, and moose. Although there is no evidence to suggest that CWD can be transmitted to humans, the possibility cannot be dismissed. Given similarities between CWD and other TSE diseases that cause human death (e.g., variant Creutzfeld-Jakob disease), wildlife agencies are concerned that possible unknown risks associated with CWD will erode hunters' willingness to hunt in states where the disease is found. This thesis presents two articles that examine the extent to which hunters would quit hunting in response to CWD using data from surveys (n = 3,519) of resident and nonresident deer hunters in four states. The first paper examined how factors related and unrelated to CWD influence hunters to stop hunting deer in their state. A series of binary logistic regression models examined the influence of four dimensions of predictor variables: (a) prevalence of CWD in the state, (b) human impact, (c) perceived human health impacts from CWD, and (d) location of hunting participation (i.e., state, residency). Human death from CWD and perceived risks associated with the disease had the largest effect on hunter behavior. If CWD prevalence increases dramatically, participation in deer hunting in these four states will decrease substantially. If high prevalence is combined with human death from CWD and other significant predictors of hunter behavior, the decline will be even greater. The second paper examined the extent to which interactions between prevalence, risk, residency, and state influence individuals to stop hunting deer in the state. Prevalence was the strongest predictor of quitting hunting in the state followed by human impact and perceived risk. State and residency were weak, but statistically significant predictors. Interactions among these predictors were hypothesized to increase potential for quitting hunting in the state. Multivariate log-linear analysis highlighted significant interactions; 12 two-way interactions, 6 three-way interactions, and 1 four-way interaction were statistically significant. Decisions to quit hunting in the state interacted with each of the five factors suggesting that they all influenced hunter behavior. The significant three-way interaction among quit hunting * perceived risk * resident, for example, indicated that nonresidents of the state who perceived greater risk were more likely to quit hunting deer in the state. This analysis illustrates the complexity of understanding hunter behavior in response to CWD.
Keywords: chronic wasting disease; perceived risk; hunting